Quality of Continuous Professional Development for Automotive Engineering Productive Teachers - Dwiki Muda Yulanto; Putu Sudira; Pramudya Dwi Aristya (Jurnal Pendidikan Teknologi dan Kejuruan, 2018)
The 21st century becomes a new challenge for productive teachers in developing their competency. One of the methods for developing their competency is conducting a continuous professional development program. This study was aimed at describing the quality of the continuous professional development of Automotive Engineering productive teachers. The type of this study was a survey study which used a descriptive quantitative method. The research subjects were all of the productive teachers of Automotive Engineering in Surakarta city with the total of 76 teachers. In conducting the study, a questionnaire was used as the data collection technique. Data analysis techniques consisted of editing, tabulating, analyzing and interpreting, and concluding. The results showed the quality of the continuous professional development of Automotive Engineering productive teachers in Surakarta city was categorized as low with the percentage of 59.2%. In conclusion, productive teachers of Automotive Engineering in Surakarta city did not actively participate in continuous professional development. The implications of this study showed that the teachers must increase self-awareness to do continuous professional development.